Quantification of the perceived training load in young female basketball players - Otaegi, A.; Los Arcos, A. (The Journal of Strength and Conditioning Research, 2020)
The purposes of this study were (a) to compare training session, match, and weekly perceived training load (TL) between U15 and U16 female basketball players and (b) within the teams, to assess the relationship between perceived TL and the changes in physical fitness performance during an in-season 9-week period. Twenty-one female players from U15 and U16 female teams from the same Spanish club participated in the study. Before and after the study, players were tested to determine physical fitness performance (using Yo-Yo IR1, countermovement jump, T-Test, and 15 m sprint). Each player declared her perceived exertion (PE) for the whole training session and match using Foster's 0-10 scale. Training week perceived TL was higher for the U16 players than the U15 players; U16 players considered the training and matches to be more difficult. In both teams, the perceived TL of the last training session of the week was significantly lower (Effect sizes = large-very large) than the other sessions. Although substantial negative associations (r = 0.52-0.78) were detected between the changes in physical fitness performance and the accumulated volume, sum of PEs and perceived TL in the U15 players, these associations were unclear in the U16 players. The basketball coaches-periodized training goals are to attain the highest session perceived TLs in the middle of the week and to reduce it considerably in the last training session. The U16 and U15 players accumulated perceived TL in different ways. Although the practice volume was similar in both teams, the older players consider the sessions more difficult. The relationship between the perceived TL and the changes in physical fitness performance varied between teams. Based on our findings, we propose that the PE-based dose-response model should be applied with caution in young female basketball players.